The Influence of Flipcharts Educational Media on the Level of Mother’s Knowledge, Mother’s Attitudes and Children's OHIS - Willia Novita Eka Rini; Zukhairina Zukhairina (The International Science of Health Journal, 2024)
Dental caries in children is a public health problem that is difficult to control. Even though it is not life-threatening, dental caries affects the growth and development of children. The aim of this research is to see the effect of flipchart media on the level of maternal knowledge, maternal attitudes and children's OHIS scores. The research was conducted using a quasi-experimental design on 20 mother and child. Data analysis used the Wilcoxon test. The research results showed significant differences in maternal knowledge, maternal attitudes and children's OHIS. Flipcart educational media has been proven to be able to increase maternal knowledge, maternal attitudes and reduce children's OHIS